A Medieval Storybook - Kingsbury, Alison Mason, 1898-; Bishop, Morris, 1893-1973 (Book collections on Project MUSE., 2013)
From the rich store of medieval tales, Morris Bishop brings together a delightful collection of thirty-five stories. Some are romantic, some religious, some realistic, some even scurrilous. There are merry tales and moral tales, sagas, allegories, and fables. They vary widely in theme and their characters represent every class of medieval society. The tales in A Medieval Storybook vividly illustrate medieval life and thought. Above all they excel as stories, and demonstrate the high level attained by narrative art in the Middle Ages and the great gift the medieval writers had for creating lively and memorable characters. Some of the stories in the book were translated by Bishop; others were translated in the nineteenth and early twentieth centuries. Line drawings by Alison Mason Kingsbury add considerably to the charm of this collection.